PREVENTIVE ASPECTS OF PREECLAMPSIA - Huertas, Erasmo (2015)
This paper refers to primary prevention of preeclampsia. As preeclampsia etiology is unknown and no trustworthy screening tests exist, it is difficult to develop rational prevention strategies. Current prevention strategies are basically nutritional supplementation and pharmacologic therapy.